THE PROBLEMS OF SEISMOACOUSTICAL INVESTIGATION OF DISSIPATION AND DISPERSION PROPERTY OF GEOLOGICAL ENVIRONMENT - PRODAIVODA, G.; MASLOV, B. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The method of solution of dynamical equation by method of Grin function presented in the form of statically and dynamical components is considered.